Servant versus directive leadership and promotability: does leader gender matter? - Barthel, Anna D. T.; Buengeler, Claudia (Frontiers in Psychology, 2023)
Are leaders more promotable when they show servant or directive leadership – and does this hold for women and men alike? Servant leaders are likely seen as more effective, likable, and thus promotable but less prototypical than directive leaders. We argue that differing degrees of communion (i.e., warmth, morality) and agency (i.e., competence, dominance) underlie the relationship of servant and directive leadership with leaders’ promotability. Based on expectancy-violation theory, we assume that men benefit more from servant leadership and women benefit more from directive leadership. Servant leadership aligns more with communion and stereotypes about women. In contrast, directive leadership aligns more with agency and stereotypes about men. These differences may result in gender-biased evaluations threatening fairness in leadership promotions. In a pre-study, servant leadership was more expected of women leaders than of men leaders. However, directive leadership was equally expected of women leaders and men leaders. An experimental vignette study (N = 454) revealed that servant leaders were seen as more effective, likable, and promotable than directive leaders, regardless of gender. Perceived leader warmth, morality, and competence were positively, and dominance was negatively, related to leader effectiveness and leader liking, which were positively related to leader promotability. We also investigated whether raters’ gender role beliefs influenced the evaluations, which they did not (as reported in the supplements). Concluding, women and men profit equally from exhibiting servant compared to directive leadership.